2011
DOI: 10.1016/j.appet.2011.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Measuring beliefs about gluten free diet adherence in adult coeliac disease using the theory of planned behaviour

Abstract: The theory of planned behaviour (TPB) was used to elicit the salient beliefs about gluten free diet (GFD) adherence in adults with coeliac disease (CD) and to design a TPB questionnaire to predict adherence levels. This questionnaire was administered to 265 CD participants with adherence and quality of life (QOL) measures, a GFD knowledge test, and self-reported psychiatric history. Regression analyses were used to test the fit of the TPB in predicting adherence, and to determine the nature of the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 22 publications
12
93
2
4
Order By: Relevance
“…Our findings add to those from other n.j.hall@durham.ac.uk (Nicola Hall) Not for publication -Tel: +44 (0) 191 33 4 0464 / Fax: +44 (0) 191 33 40361 10 studies looking at the association between concepts from existing theories of health behaviour (Ford et al, 2012;Leffler et al, 2008;Sainsbury & Mullan, 2011), by demonstrating the importance of this distinction in understanding adherence to the GFD. Both types of non-adherence are common with only 28% of respondents reporting not having consumed any gluten at all over the last six months and 40%…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our findings add to those from other n.j.hall@durham.ac.uk (Nicola Hall) Not for publication -Tel: +44 (0) 191 33 4 0464 / Fax: +44 (0) 191 33 40361 10 studies looking at the association between concepts from existing theories of health behaviour (Ford et al, 2012;Leffler et al, 2008;Sainsbury & Mullan, 2011), by demonstrating the importance of this distinction in understanding adherence to the GFD. Both types of non-adherence are common with only 28% of respondents reporting not having consumed any gluten at all over the last six months and 40%…”
Section: Discussionsupporting
confidence: 62%
“…Adherence to the GFD is reported to range between 36%-96% and is associated with a variety of demographic, psychosocial and clinical factors (Ford, Howard & Oyebode, 2012;Hall, Rubin & Charnock, 2009;Sainsbury & Mullan, 2011). Adherence is not usually conceptualised in behavioural terms, despite the acknowledgement of both n.j.hall@durham.ac.uk (Nicola Hall) Not for publication -Tel: +44 (0) 191 33 4 0464 / Fax: +44 (0) 191 33 40361 4 intentional and inadvertent gluten consumption within the literature (Black & Orfila, 2011;Casellas, Lopez & Malagelada, 2006;Dewar et al, 2012;Vahedi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The decision to use the single item rather than the entire scale to measure QOL was based on the significant and positive correlations observed between overall QOL and each of the domain scores in a previous sample of patients with CD (29). The Depression Anxiety Stress Scale (48,49) was used to measure the negative emotional states of depression (e.g., "I felt downhearted and blue"), anxiety ("I felt I was close to panic"), and stress ("I tended to overreact to situations").…”
Section: Methodsmentioning
confidence: 99%
“…; medical (e.g., gastrointestinal symptoms, whereby more severe symptoms are associated with poorer QOL) (22)(23)(24)(25)(26)(27); and dietary (e.g., GFD adherence, whereby poorer adherence is associated with poorer QOL; and perceived difficulty of adherence, which was also associated with poorer QOL) (23,(28)(29)(30) aspects of the disease. While these factors are important for QOL, one area that has received less attention is psychological symptoms and coping, despite higher rates of psychological symptoms within CD patients compared to the general population (16,(31)(32)(33)(34)(35)(36).…”
Section: )mentioning
confidence: 99%
“…Considering that gluten is a constitutive protein of wheat and other grains and that baked products and pasta are staple elements of the Western diet, a high number of patients end up facing the sudden change of their eating habits and their families' daily routine (13,14). Furthermore, GFD is highly restrictive and recent data have shown that patients report a substantial treatment burden similar or higher than many other chronic conditions in spite of a good long-term prognosis (15), leading to multiple limitations in common social activities and complaining of psychological distress, anxiety and social phobia (16)(17)(18). Therefore, given its chronic nature and the possible complications (i.e., autoimmune and/or neoplastic diseases, anemia and osteoporosis), CD requires on-going medical support, which has shown to improve the disease outcome and patients' compliance to GFD (19).…”
Section: Introductionmentioning
confidence: 99%